(since the given equation uses bb as a variable, we will need to express the quadratic formula, which normally uses bb as a constant, with some variant, hatbˆb.
To help reduce confusion, I will rewrite the given f(b)f(b)as
color(white)("XX")f(x)=x^2-4x+4=0XXf(x)=x2−4x+4=0
For the general quadratic form:
color(white)("XX")hatax^2+hatbx+hatc=0XXˆax2+ˆbx+ˆc=0
the solution given by the quadratic equation is
color(white)("XX")x=(-hatb+-sqrt(hatb^2-4hatahatc))/(2hata)XXx=−ˆb±√ˆb2−4ˆaˆc2ˆa
With hata = 1ˆa=1, hatb=-4ˆb=−4, and hatc=+4ˆc=+4
we get
color(white)("XX")b=(x=)(4+-sqrt((-4)^2+4(1)(4)))/(2(1))XXb=(x=)4±√(−4)2+4(1)(4)2(1)
as the quadratic formula